2009
DOI: 10.1164/rccm.200810-1584oc
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Decreases Lipopolysaccharide-induced Pulmonary Inflammation in Healthy Volunteers

Abstract: Rationale: Simvastatin inhibits inflammatory responses in vitro and in murine models of lung inflammation in vivo. As simvastatin modulates a number of the underlying processes described in acute lung injury (ALI), it may be a potential therapeutic option. Objectives: To investigate in vivo if simvastatin modulates mechanisms important in the development of ALI in a model of acute lung inflammation induced by inhalation of lipopolysaccharide (LPS) in healthy human volunteers. Methods: Thirty healthy subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
188
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(198 citation statements)
references
References 49 publications
6
188
0
4
Order By: Relevance
“…We used simvastatin at a dose of 80 mg on the basis of our previous data from clinical studies, 4,5 in which simvastatin improved surrogate outcomes and biologic mechanisms implicated in ARDS. The data from our current study and the SAILS trial show that neither a lipophilic statin (simvastatin) nor a hydrophilic statin (rosuvastatin) is effective in the treatment of ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used simvastatin at a dose of 80 mg on the basis of our previous data from clinical studies, 4,5 in which simvastatin improved surrogate outcomes and biologic mechanisms implicated in ARDS. The data from our current study and the SAILS trial show that neither a lipophilic statin (simvastatin) nor a hydrophilic statin (rosuvastatin) is effective in the treatment of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Simvastatin reduced pulmonary and systemic inflammatory responses in a human model of ARDS induced by lipopolysaccharide inhalation. 4 In addition, in a small, single-center, randomized, placebo-controlled study involving patients with acute lung injury, simvastatin ameliorated nonpulmonary organ dysfunction and was safe. 5 That phase 2 study was not designed or powered to show an effect of simvastatin on clinical outcomes.…”
mentioning
confidence: 99%
“…Pretreatment with simvastatin reduced endotoxin-induced alveolar neutrophilia, myeloperoxidase, TNF-a, and matrix metalloproteinases 7, 8, and 9. Thus, this clinical study paves the way for further therapeutic evaluation of statins in patients with ALI (70).…”
Section: Treatment Of Acute Lung Injury and Other Critical Illnesses:mentioning
confidence: 78%
“…A metaanalysis of 13 studies involving 254,950 patients found that treatment with statins in community-acquired pneumonia was associated with improved survival but that the effect was more pronounced if treatment was initiated in the community prior to hospital admission [15]. This is supported by data that pretreatment with simvastatin attenuated the systemic and pulmonary inflammatory response to lipopolysaccharide (LPS) in healthy human subjects [10]. Future studies could focus on randomising patients at high risk of ARDS, such as patients undergoing high-risk surgery such as oesophagectomy, to pretreatment with statins.…”
mentioning
confidence: 97%
“…As for sepsis, data from recent large, multicentre, double-blind, randomised, placebo-controlled clinical trials in patients with ARDS have shown that, despite promising findings in preclinical and early phase clinical trials [9,10], statins did not significantly improve clinical outcomes [11,12]. When secondary endpoints were analysed, rosuvastatin was associated with a small decrease in liver and renal failure-free days [13].…”
mentioning
confidence: 99%